Інформація як кіберзброя у сучасному світі - Гірман, Алла Павлівна (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
The rapid development of electronic technology and its growing integration into all spheres of life, including government and military administration, have led to a new kind of confrontation between states known as “information warfare”. Specific means are being developed to conduct information warfare, which can be used both for defense and for attack. These can be controlled programs to destroy or distort information, block access to important data or disorganize the work of information resources, software viruses, intelligence programs, etc. Today, there are standard tools for detecting vulnerabilities in information systems. However, there is an urgent need to create a protection system with several levels, due to the possibility of interaction of all modern information systems through a single global communication network for users of any level.